2021
DOI: 10.3390/jpm11010058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Homeostasis in the Soft Tissue of the Periodontium: A Narrative Review

Abstract: Aging is characterized by a progressive decline or loss of physiological functions, leading to increased susceptibility to disease or death. Several aging hallmarks, including genomic instability, cellular senescence, and mitochondrial dysfunction, have been suggested, which often lead to the numerous aging disorders. The periodontium, a complex structure surrounding and supporting the teeth, is composed of the gingiva, periodontal ligament, cementum, and alveolar bone. Supportive and protective roles of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 135 publications
1
14
0
1
Order By: Relevance
“…Consequently, GMSCs exhibit higher levels of growth factor receptors that assist in enhanced cellular proliferation and maintenance of tissue homeostasis ( 46 , 49 ). An associated enhancement in the expression of PDGFR, FGFR, and EGFR in our experiments supported the above reports about sustenance of gingival health under the conditions of frequent microbial insults and increasing inflammatory environment with age ( 49 52 ). Nevertheless, we observed higher senescent population and increase in PDT of GMSCs derived from elderly donors, which signify impairment in stemness due to extensive in vitro passaging, although the rate of in vitro senescence in old GMSCs is slower as compared to their young counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, GMSCs exhibit higher levels of growth factor receptors that assist in enhanced cellular proliferation and maintenance of tissue homeostasis ( 46 , 49 ). An associated enhancement in the expression of PDGFR, FGFR, and EGFR in our experiments supported the above reports about sustenance of gingival health under the conditions of frequent microbial insults and increasing inflammatory environment with age ( 49 52 ). Nevertheless, we observed higher senescent population and increase in PDT of GMSCs derived from elderly donors, which signify impairment in stemness due to extensive in vitro passaging, although the rate of in vitro senescence in old GMSCs is slower as compared to their young counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Aging reduces gingival fibroblast proliferation and migration, fiber density, organic matrix production, and cellular mitotic activity in the periodontal ligament. Meanwhile, aging increases mRNA levels of MMP-2, MMP-8, which promote extracellular matrix degradation ( 189 ).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Aging may affect periodontal tissues by altering the host response. There is reduced effectiveness of the adaptive immune response with aging ( 189 ). Aged mice have reduced recruitment of dendritic cells in response to bacterial challenge, which may be due to reduced DC migration caused by high glucose levels or high levels of advanced glycation end products ( 190 ).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Many studies have shown various materials such as fibrin-/silk- [ 15 ], polysaccharide- [ 16 ], and collagen-based adhesives [ 17 ], which can be used as soft hydrogels for hemostasis. Collagen is one of the essential extracellular matrices in gingival tissues [ 18 ]. As such, collagen-based soft hydrogels have been an option for use in oral/dental hemostasis.…”
Section: Introductionmentioning
confidence: 99%